A rare presentation of deep infiltrating cervical endometriosis mimicking cervical cancer - Swetha, P.; Nagashree, U.; Kondammal, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Though endometriosis is a common progressive benign disorder of women, endometriosis of the cervix is rarely seen. It poses a challenge both for diagnosis and management. Most of the patients with Cervical endometriosis are asymptomatic, present with abnormal vaginal bleeding, post-coital bleeding or intermenstrual bleeding. In this paper, we report a rare case of deep infiltrating cervical endometriosis involving the ureter mimicking cervical cancer, the need for awareness to include cervical endometriosis as a differential diagnosis in case of menstural irregularities and its potential to cause serious complications.